English Language Training to Enhance Community Communication Skills in the Era of Globalization - Susiandari, Ariawati (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
In the era of globalization, English has become a key tool for communication in various aspects of life, including education, business, and social interaction. However, many communities still lack sufficient English proficiency, which limits their opportunities for growth and development. This community service program aimed to provide English language training to improve communication skills among community members. The program was carried out through workshops, interactive learning sessions, and practical communication exercises. The results showed an increase in participants’ confidence and ability to use English in daily interactions and professional contexts. This initiative demonstrates that community-based English training can effectively enhance communication skills and prepare individuals to face global challenges.